Rekayasa Proses Produksi Nira Bit (Beta vulgaris L.) sebagai Alternatif Pemanis Alami - Ameliya (Fakultas Teknologi Pertanian, 2025)
The sugar demand exceeding domestic sugarcane production drives to the dependence on sugar import rate in Indonesia. Beetroot (Beta vulgaris L.) offers a potential sugar commodity resource for alternative natural sweetener due to the high sucrose content and the cultivation efficiency. This study aims to determine the best extraction technique for beet juice production and analyze the effect of temperature (30 °C, 45 °C, 60 °C) and duration of extraction (30, 60, 90 minutes). Some physicochemical characteristics are analyzed and the best conditions was determined by using a factorial Completely Randomized Design. The grating technique in size reduction of beetroot before extraction was selected in this study because it produces a higher yield of reducing sugar (2.33%) and total sugar (9.535 g/L) compared to blending technique. The beetroots juice was extracted by using distilled water as solvent (ratio of 1:2), and some physicochemical properties was tested including yield, color, total soluble solids (TSS), pH, reducing sugars, and total sugars, and then the data were statistically analyzed using ANOVA, Tukey HSD, and De Garmo effectiveness tests. The results showed that temperature of 60°C and 60 minutes (A3B2) produced the highest yield (4.16%), TSS (3.533% brix), reducing sugar (4.591 g/L), and total sugar (15.904 g/L), with an effectiveness value of 0.82. Temperature and duration have a significant effect (p<0.05) on most parameters. This study concluded that extraction at a temperature of 60°C for 60 minutes is the best condition to produce high-quality beetroot juice as a natural sweetener.
Entry oleh Arif 2026 Januari 30
Keywords: Beetroot; Extraction; Grating; Natural Sweetener; Physicochemical